Extraction of vertical cylinder contacting area for motorcycle safety verification. Issue 4 (4th July 2018) - Inui, Masatomo; Umezu, Nobuyuki
ABSTRACT: Japanese motorcycle manufacturers define a safety regulation regarding the motorcycle shape to prevent injury to pedestrians in the event of a crash. To satisfy the regulation, the external surface of the motorcycle must have a sufficient degree of roundness if there is any chance that it could contact a vertical cylinder having a diameter of 300 mm approximating the human body. In this paper, we propose a novel method for assisting in the safety regulation inspection. This method extracts the surface regions of the tessellated motorcycle body where the vertical cylindrical column contacts and the surface region radius is less than 4 mm. The parallel processing capability of a graphics processing unit (GPU) is used to accelerate the extraction task of identifying the column contacting area. A system using our algorithm can detect surface areas on the motorcycle body where the safety regulation is not satisfied. GRAPHICAL ABSTRACT: